The Relationship between Total Quality Management and Financial Performance: Evidence from Morocco - Belkasseh, Mohammed (Archives of Business Research, 2019)
The author attempts to explore the effect of TQM implementation on financial performance indicators evolution. A quantitative study was conducted on Moroccan companies listed on Casablanca Stock Exchange according to a methodological sorting connected to TQM implementation. The observation focused on the evolution of the turnover and the operating income before and after TQM. The objective observation of the results makes it possible to confirm that an effective TQM implementation positively impacts the development of companies’ financial performance indicators. A very interesting path forward of the study concerns a situational determinant: the economic crisis to understand the variations observed over the defined periods of study. This study was undertaken methodologically independently from the aim to study a state of crisis. As such, the author suggests that an effective TQM implementation would allow companies to "immunize" themselves against the uncertainties of an unfavorable economic situation.